The Impact of Study Lesson in Conquering Narrative Challenges: AI Wordwall as Your Ally - Saptanawati, Imelda; Murtiastuti, Sri; Afianti, Dewintha (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2022)
The purpose of this study is to inquire at the impact of applying case-based learning in addressing issues connected to comprehending and mastering narrative texts among 9th-grade junior high school students. The research focuses on the use of the Professional Learning Community (PLC) approach, with AI Wordwall serving as a supporting tool. The data obtained through interviews and observations with 9th-grade students, English Panel teachers, and postgraduate students in English education who engaged in lesson study practices was evaluated using an open coding system. Despite the use of Professional Learning Communities (PLC) as a platform for teacher collaboration, this research shows that junior high schools, particularly those in the ninth grade, still require full preparation for this new approach. This study's findings suggest that implementing AI Wordwall into the PLC framework, in particular, can dramatically boost students' confidence levels. This article explains how a case-based learning strategy, aided by AI technologies such as Wordwall, may help students overcome barriers to reading narrative texts in junior high school. These findings suggest ways to improve the PLC method while also improving learning outcomes and student confidence in the contemporary era of digital educationThis study investigates how case-based learning can help 9th-grade students better understand and learn narrative texts. It uses a Professional Learning Community (PLC) approach and AI Wordwall as a supporting tool. The researchers collected data from 9th-grade students, English teachers, and postgraduate students in English education through interviews and observations. The results show that while PLCs are used for teacher collaboration, 9th-grade classes in junior high schools are not fully prepared for this new approach. However, incorporating AI Wordwall into the PLC framework significantly improved students' confidence levels. The study demonstrates that combining case-based learning with AI tools like Wordwall can help students overcome difficulties in reading narrative texts. These findings offer suggestions for enhancing the PLC method and improving learning outcomes and student confidence in the digital education era.